Negative electrode material for lithium-ion secondary battery, negative electrode material composition for lithium-ion secondary battery, negative electrode for lithium-ion secondary battery, and lithium-ion secondary battery

CN116897447BActive Publication Date: 2026-10-27RESONAC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280012768.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-02
Filing Date
2022-01-26
Publication Date
2026-10-27
Estimated Expiration
2042-01-26

AI Technical Summary

Benefits of technology

[0036]本公开的一个方式能够提供一种能够制造放电容量优异且可抑制锂金属的析出并且Li析出耐性优异的锂离子二次电池的锂离子二次电池用负极材料、以及包含该锂离子二次电池用负极材料的锂离子二次电池用负极材料组合物、锂离子二次电池用负极、和锂离子二次电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004369741770000331
    Figure BDA0004369741770000331
  • Figure BDA0004369741770000381
    Figure BDA0004369741770000381
  • Figure BDA0004369741770000391
    Figure BDA0004369741770000391
Patent Text Reader

Abstract

A negative electrode material for a lithium ion secondary battery, which is a graphite particle satisfying the following conditions: if a compression load required for compaction to 1.7 g / cm 3 in an Autograph measurement is set to x (kN / cm 2 ), then x ≥ 2.0, if a particle diameter at which a cumulative from a small diameter side in a particle size distribution on a volume basis measured by a laser diffraction method reaches 50% is set to y (μm), then 5.0 ≤ y ≤ 20.0, the x and y satisfy the following formula (1), and a graphitization degree satisfies greater than or equal to 90.0%. 11.3x - 0.66y + 1.4 ≥ 14.5 … (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to negative electrode materials for lithium-ion secondary batteries, negative electrode material compositions for lithium-ion secondary batteries, negative electrodes for lithium-ion secondary batteries, and lithium-ion secondary batteries. Background Technology

[0002] Lithium-ion rechargeable batteries, leveraging their small size, lightweight nature, and high energy density, have long been widely used in electronic devices such as laptop PCs, mobile phones, smartphones, and tablet PCs. In recent years, against the backdrop of environmental problems such as global warming caused by CO2 emissions, electric vehicles (EVs) powered solely by batteries, hybrid electric vehicles (HEVs) combining gasoline engines and batteries, and plug-in hybrid electric vehicles (PHEVs) have become increasingly popular. As a result, the development of lithium-ion rechargeable batteries (on-board lithium-ion rechargeable batteries) for use in these vehicles is underway.

[0003] The performance of the negative electrode material in lithium-ion secondary batteries has a significant impact on the input characteristics of the batteries. Carbon materials are widely used as negative electrode materials for lithium-ion secondary batteries. For example, highly crystallized carbon materials such as artificial graphite and spherical natural graphite (obtained by spheroidizing flake-like natural graphite) have been proposed as materials for obtaining high-density negative electrodes.

[0004] As an example of artificial graphite, Patent Document 1 discloses a negative electrode material for lithium-ion secondary batteries containing composite particles, wherein the composite particles comprise multiple flat graphite particles and spherical graphite particles aggregated or combined in a manner where the orientation planes are not parallel. Additionally, Patent Document 2 discloses a negative electrode active material for lithium-ion secondary batteries containing carbon powder particles, wherein the carbon powder particles have a morphology of plate-like particles stacked along a plane orientation to form a primary stable structure, and micropores are formed on the surface.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: International Publication No. 2015 / 147012

[0008] Patent Document 2: Japanese Patent Application Publication No. 2005-302725 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] With the rapid growth of the EV market, the demand for negative electrode materials for lithium-ion rechargeable batteries is constantly increasing. Among them, the need for increased discharge capacity and fast charging to improve convenience is deeply rooted, requiring high-rate charging in the negative electrode active materials.

[0011] The challenge with such high-rate charging is that the decrease in IR due to the large current can prevent some lithium ions from inserting into the graphite layers, causing lithium metal to deposit on the surface of the graphite particles. When lithium metal deposits in needle-like shapes, it can puncture the separator, causing an internal short circuit and leading to thermal runaway.

[0012] Considering the above aspects, it is desirable to manufacture a negative electrode material for lithium-ion secondary batteries that can suppress lithium metal deposition and has excellent lithium (Li) deposition resistance.

[0013] In view of the above, one aspect of this disclosure is to provide a negative electrode material for a lithium-ion secondary battery that can manufacture a lithium-ion secondary battery with excellent discharge capacity, suppression of lithium metal deposition, and excellent Li deposition resistance, as well as a negative electrode material composition for a lithium-ion secondary battery comprising the negative electrode material for a lithium-ion secondary battery, a negative electrode for a lithium-ion secondary battery, and a lithium-ion secondary battery.

[0014] Another objective of this disclosure is to provide a negative electrode material for a lithium-ion secondary battery capable of manufacturing a lithium-ion secondary battery with excellent resistance to lithium metal deposition and Li deposition, as well as a negative electrode material composition for a lithium-ion secondary battery comprising the negative electrode material, a negative electrode for a lithium-ion secondary battery, and a lithium-ion secondary battery.

[0015] Methods for solving problems

[0016] The methods used to solve the above problems include the following approaches.

[0017] <1> A negative electrode material for lithium-ion secondary batteries, comprising graphite particles as follows: If, in Autograph measurements, the particles are compacted to 1.7 g / cm³... 3 The required compression load is set as x (kN / cm). 2 If x ≥ 2.0, and if the particle size at which the cumulative particle size distribution from the small diameter side reaches 50% in the volume reference particle size distribution determined by laser diffraction is set as y (μm), then 5.0 ≤ y ≤ 20.0, and the above x and y satisfy the following equation (1), and the degree of graphitization satisfies greater than or equal to 90.0%.

[0018] 11.3x - 0.66y + 1.4 ≥ 14.5…(1)

[0019] <2> A negative electrode material for lithium-ion secondary batteries, which is graphite particles such that when a negative electrode material layer is formed using the negative electrode material for lithium-ion secondary batteries, the ratio of the tortuous path length L (μm) of the distance from one surface to another in the thickness direction through the void inside the negative electrode material layer to the thickness T (μm) of the negative electrode material layer, i.e., L / T, satisfies less than or equal to 1.7.

[0020] <3> The peak intensity (I002 diffraction line) of the negative electrode material for lithium-ion secondary batteries, formed using the negative electrode material for lithium-ion secondary batteries, and subjected to X-ray diffraction measurement on the negative electrode after being pressed at 0.8 t / cm, is obtained. 002 The peak intensity of the 110 diffraction line (I) 110 The ratio of I to ) 002 / I 110 Less than or equal to 350.

[0021] <4> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <3> has not undergone the treatment of coating the surface of the graphite particles with low-crystallinity carbon.

[0022] <5> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <4>, if the value measured by Raman spectroscopy is at 1300 cm⁻¹ -1 ~1400cm -1 Peak intensity within the range (I) D ) and at 1580cm -1 ~1620cm -1 Peak intensity within the range (I) G The ratio of I to ) D / I G If we define it as the R value, then the R value of the above graphite particles is 0.10 to 0.40.

[0023] <6> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <5> has undergone a treatment of coating the surface of the above-mentioned graphite particles with low-crystallinity carbon.

[0024] If the value measured by Raman spectroscopy is at 1300 cm⁻¹ -1 ~1400cm -1 Peak intensity within the range (I) D ) and at 1580cm -1 ~1620cm -1 Peak intensity within the range (I) G The ratio of I to ) D / I G If we define it as the R value, then the R value of the above graphite particles is 0.20 to 0.60.

[0025] <7> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <6> has a particle size of 0.1 μm to 7.0 μm when the cumulative particle size distribution on a volume basis determined by laser diffraction reaches 10% from the small diameter side.

[0026] <8> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <7> has a zero-tap density of 0.3 g / cm³. 3 ~0.6g / cm 3 .

[0027] <9> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <8> has a tap density of 0.4 g / cm³ after 30 vibrations. 3 ~0.7g / cm 3 .

[0028] <10> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <9> has a tap density of 0.7 g / cm³ after 250 vibrations. 3 ~1.1g / cm 3 .

[0029] <11> The specific surface area of ​​the graphite particles, determined by nitrogen adsorption measurement at 77 K, according to any one of <1> to <10> for the negative electrode material of lithium-ion secondary batteries, is 0.2 m². 2 / g~6.0m 2 / g.

[0030] <12> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <11> has a particle size distribution D90 / D10 of 3.0 to 7.0 for the graphite particles.

[0031] <13> The negative electrode material for lithium-ion secondary batteries according to any one of <1> to <12>, wherein the graphite particles comprise composite particles formed by the aggregation or combination of multiple graphite particles.

[0032] <14> A negative electrode material composition for lithium-ion secondary batteries, comprising any one of <1> to <13>, a binder, and a solvent.

[0033] <15> A negative electrode for a lithium-ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises any one of <1> to <13> for a lithium-ion secondary battery.

[0034] <16> A lithium-ion secondary battery comprising the negative electrode, positive electrode and electrolyte described in <15> for a lithium-ion secondary battery.

[0035] Invention Effects

[0036] One aspect of this disclosure provides a negative electrode material for a lithium-ion secondary battery capable of manufacturing a lithium-ion secondary battery with excellent discharge capacity, suppression of lithium metal deposition, and excellent Li deposition resistance, as well as a negative electrode material composition for a lithium-ion secondary battery comprising the negative electrode material, a negative electrode for a lithium-ion secondary battery, and a lithium-ion secondary battery.

[0037] Another aspect of this disclosure provides a negative electrode material for a lithium-ion secondary battery capable of manufacturing a lithium-ion secondary battery with excellent resistance to lithium metal deposition and Li deposition, as well as a negative electrode material composition for a lithium-ion secondary battery comprising the negative electrode material, a negative electrode for a lithium-ion secondary battery, and a lithium-ion secondary battery. Attached Figure Description

[0038] Figure 1 This is an example of a chart used to evaluate Li precipitation resistance. Detailed Implementation

[0039] The following describes in detail the methods for carrying out the present invention. However, the present invention is not limited to the following embodiments. In the following embodiments, the constituent elements (including element steps, etc.) are not essential unless specifically stated otherwise. Similarly, numerical values ​​and their ranges are not intended to limit the present invention.

[0040] In this disclosure, the term "process" includes not only processes that are independent of other processes, but also processes that can be clearly distinguished from other processes if their purpose can be achieved.

[0041] In this disclosure, the numerical range represented by “~” includes the minimum and maximum values ​​recorded before and after “~”, respectively.

[0042] In the numerical ranges described in this disclosure, the upper or lower limit of one numerical range can be replaced by the upper or lower limit of another numerical range described in other stages. Furthermore, the upper or lower limit of the numerical ranges described in this disclosure can also be replaced by the values ​​shown in the embodiments.

[0043] In this disclosure, each component may contain multiple substances equivalent to each component. When multiple substances equivalent to each component are present in the composition, unless otherwise specified, the content or percentage of each component refers to the total content or percentage of the multiple substances present in the composition.

[0044] In this disclosure, the particles corresponding to each component may include multiple types. When multiple particles corresponding to each component are present in the composition, unless otherwise specified, the particle size of each component refers to the value relative to the mixture of the multiple particles present in the composition.

[0045] In this disclosure, the term "layer" or "membrane" includes, in addition to the case where it is formed in the entire region when the region where the layer or membrane is observed, the case where it is formed only in a part of the region.

[0046] In this disclosure, the term "layer stacking" means stacking layers, which can be two or more layers combined, or two or more layers that are detachable.

[0047] In this disclosure, the particle size distribution of primary particles contained in the negative electrode material and composite particles can be determined using a laser diffraction particle size distribution measuring device. The average particle size is the particle size (D50) at which the cumulative particle size distribution from the small diameter side in the volume-based particle size distribution reaches 50%. D99.9 is the particle size at which the cumulative particle size distribution from the small diameter side in the volume-based particle size distribution reaches 99.9%, D90 is the particle size at which the cumulative particle size distribution from the small diameter side in the volume-based particle size distribution reaches 90%, and D10 is the particle size at which the cumulative particle size distribution from the small diameter side in the volume-based particle size distribution reaches 10%.

[0048] Negative electrode materials for lithium-ion secondary batteries

[0049] Hereinafter, the negative electrode material for lithium-ion secondary batteries according to the present disclosure will be described in turn according to the first embodiment and the second embodiment. It should be noted that the present invention is not limited to these embodiments.

[0050] [First Implementation Method]

[0051] The first embodiment of this disclosure relates to a negative electrode material for lithium-ion secondary batteries (hereinafter, also simply referred to as negative electrode material) as graphite particles with the following properties: [The text abruptly ends here, so the translation stops as well.] 3 The required compression load is set as x (kN / cm). 2 If x ≥ 2.0, and if the particle size at which the cumulative particle size distribution from the small diameter side reaches 50% in the volume reference particle size distribution determined by laser diffraction is set as y (μm), then 5.0 ≤ y ≤ 20.0, and the above x and y satisfy the following equation (1), and the degree of graphitization satisfies greater than or equal to 90.0%.

[0052] 11.3x - 0.66y + 1.4 ≥ 14.5…(1)

[0053] By using the negative electrode material of the first embodiment, it is possible to manufacture a lithium-ion secondary battery with excellent discharge capacity, suppression of lithium metal deposition, and excellent lithium (Li) deposition resistance. The reason for this can be inferred, for example, as follows: Since the graphitization degree of the graphite particles is greater than or equal to 90.0%, there is a tendency for excellent discharge capacity when manufacturing a lithium-ion secondary battery.

[0054] In lithium-ion secondary batteries, during charging, lithium ions begin to be inserted into graphite particles on the surface of the negative electrode, gradually shifting to insertion into graphite particles located deeper within the electrode. The inventors believe that by reducing the time difference between the charging reaction on the surface and deeper parts of the negative electrode, lithium metal deposition during charging can be suppressed. The reasons are as follows: Because lithium ions can diffuse to the deeper parts of the current collector in a short time, the amount of active material capable of reacting with lithium ions increases, and the effective reaction area increases compared to the applied current, resulting in a decrease in internal resistance. Therefore, it is believed that the IR drop is smaller, and the negative electrode potential can be maintained at a higher level, thus increasing the time to reach the lithium deposition initiation potential and the amount of charge.

[0055] Here, it is hypothesized that by reducing the particle size of graphite particles, the distance that lithium ions need to travel from the surface of the negative electrode to the graphite particles deep within the negative electrode can be shortened.

[0056] By increasing the compressive load required to compact graphite particles to a specific density, the graphite particles are less likely to be crushed when used as a negative electrode material. As a result, the lithium-ion pathway becomes less prone to blockage. It is speculated that the distance lithium ions need to travel from the surface of the negative electrode to the graphite particles deep within the negative electrode can be shortened.

[0057] As described above, by reducing the particle size of graphite particles and increasing the compressive load of graphite particles, the distance that lithium ions travel from the surface of the negative electrode to the graphite particles deep within the negative electrode can be shortened. As a result, it is believed that the time difference between the charging reaction at the surface of the negative electrode and at its depth can be reduced. Furthermore, the inventors have discovered that by satisfying the above equation (1) with the particle size and compressive load of the graphite particles, the suppression of lithium metal deposition during charging is effective, thereby improving Li deposition tolerance.

[0058] (Compression load)

[0059] As long as the compressive load of the graphite particles represented by x in equation (1) is greater than or equal to 2.0 kN / cm 2 Furthermore, there is no particular limitation on the value that satisfies the above equation (1). For example, from the viewpoint of appropriately suppressing the deformation of graphite particles caused by the pressing during the production of the negative electrode, the compressive load of the graphite particles is preferably greater than or equal to 2.3 kN / cm. 2 More preferably, greater than or equal to 2.5 kN / cm2 Further preferred value is greater than or equal to 2.8 kN / cm 2 A value greater than or equal to 3.0 kN / cm is particularly preferred. 2 .

[0060] From the perspective of suppressing the deformation of the current collector caused by the pressing during the fabrication of the negative electrode and the peeling of the current collector from the active material, the compressive load of the graphite particles can be less than or equal to 5.0 kN / cm. 2 It can be less than or equal to 4.5 kN / cm. 2 It can be less than or equal to 4.0 kN / cm. 2 It can also be less than or equal to 3.5 kN / cm 2 .

[0061] In this disclosure, the compressive load of the graphite particles can be calculated as follows: A predetermined mass (e.g., 3.0 g) of graphite particles is filled into a mold and compressed at a constant rate (e.g., 10 mm / min) until the density of the compressed graphite particles reaches 1.7 g / cm³. 3 Pressure at time (kN / cm) 2 Let ) be the compressive load of the graphite particles.

[0062] In the above measurements, for example, a mold with a diameter of 15 mm was used as the mold, and compression was performed using Autograph (e.g., manufactured by Shimadzu Corporation). The density of the graphite particles was calculated based on the volume and mass of the graphite particles, wherein the volume of the graphite particles was based on the bottom area of ​​the mold (e.g., 1.767 cm²). 2 The distance from the bottom of the mold to the pressing surface of the graphite particles is calculated.

[0063] The greater the compressive load on graphite particles, the less likely they are to deform or break down due to pressure.

[0064] (Average particle size)

[0065] The particle size (hereinafter also referred to as "average particle size") at which the cumulative percentage from the small diameter side reaches 50% in the volumetric particle size distribution of graphite particles determined by laser diffraction is 5.0 μm to 20.0 μm. The average particle size of graphite particles is y in equation (1).

[0066] From the viewpoint of further improving Li precipitation resistance, the average particle size of graphite particles is preferably less than or equal to 17.0 μm, more preferably less than or equal to 14.5 μm, and even more preferably less than or equal to 11.0 μm.

[0067] The average particle size of graphite can be greater than or equal to 6.0 μm or greater than or equal to 7.0 μm.

[0068] The average particle size of graphite particles can be determined using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation).

[0069] Methods for determining the average particle size of graphite particles contained in the negative electrode state include: fabricating a sample electrode, embedding the electrode in epoxy resin, mirror polishing it, and observing the electrode cross-section using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"); and fabricating the electrode cross-section using an ion polishing device (e.g., Hitachi High Technology Corporation, "E-3500") and measuring it using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"). In these cases, the average particle size is the median of the sizes of arbitrarily selected 100 particles.

[0070] From the viewpoint that lithium metal precipitation can be appropriately suppressed and lithium-ion secondary batteries with better Li precipitation resistance can be manufactured, the negative electrode material of the first embodiment preferably satisfies the following formula (2), more preferably satisfies the following formula (3), and even more preferably satisfies the following formula (4).

[0071] 11.3x - 0.66y + 1.4 ≥ 20…(2)

[0072] 11.3x - 0.66y + 1.4 ≥ 25…(3)

[0073] 11.3x - 0.66y + 1.4 ≥ 30…(4)

[0074] (D10)

[0075] The D10 of the graphite particles is preferably 0.1 μm to 7.0 μm, more preferably 0.1 μm to 6.0 μm, even more preferably 1.0 μm to 6.0 μm, and particularly preferably 2.5 μm to 5.5 μm.

[0076] The D10 of graphite particles can be determined using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation).

[0077] (Particle size distribution D90 / D10)

[0078] There is no particular limitation on the particle size distribution D90 / D10 of graphite particles. Its lower limit can be greater than or equal to 3.0, greater than or equal to 3.5, or greater than or equal to 4.0.

[0079] The upper limit of the particle size distribution D90 / D10 of graphite particles can be less than or equal to 7.0, less than or equal to 6.5, or less than or equal to 6.2.

[0080] By ensuring that the particle size distribution of graphite particles, D90 / D10, is less than or equal to 7.0, the distance that lithium ions must travel from the surface of the negative electrode to the graphite particles deep within it can be shortened. As a result, the time difference between the charging reaction at the surface and deep within the negative electrode can be reduced, thus tending to suppress lithium metal deposition during charging.

[0081] Particle size distribution D90 / D10 can be measured using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation).

[0082] Methods for determining the particle size distribution D90 / D10 of graphite particles contained in the negative electrode include: fabricating a sample electrode, embedding the electrode in epoxy resin, mirror polishing it, and observing the electrode cross-section using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"); and fabricating the electrode cross-section using an ion polishing device (e.g., Hitachi High Technology Corporation, "E-3500") and measuring it using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"). The particle size distribution D90 / D10 can then be determined using the following methods.

[0083] (1) Use binarization method to find the area Sn of the mapped particle (n is the inherent number of the selected particle).

[0084] (2) Assuming the particle is a true sphere of ideal shape, the equivalent diameter of the circle Ln = √Sn / π can be obtained from the area Sn.

[0085] (3) Calculate the volume of the sphere Vn = (4 / 3)π(Ln) from the equivalent diameter of the circle Ln. 3 .

[0086] (4) Repeat (1) to (3) for the selected 100 particles.

[0087] (5) In the distribution curve with the vertical axis set to 100% of the cumulative volume and the horizontal axis set to the particle size, the particle size at the point that intersects the horizontal axis of 10% is set to the 10% diameter (D10), and the particle size at the point that intersects the horizontal axis of 90% is set to the 90% diameter (D90), so that D90 / D10 can be calculated.

[0088] (Standard deviation of particle size distribution)

[0089] The standard deviation of the particle size distribution of graphite particles can be 0.18–0.40 or 0.25–0.35.

[0090] The standard deviation of particle size distribution can be determined using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation) based on a frequency distribution chart with the horizontal axis set to the logarithmic scale of particle size and the vertical axis set to the particle amount (%).

[0091] (degree of graphitization)

[0092] The graphite particles have a graphitization degree greater than or equal to 90.0%. From the viewpoint of discharge capacity when manufacturing lithium-ion secondary batteries, it is preferable to have a degree greater than or equal to 90.5%, more preferably greater than or equal to 91.0%, and even more preferably greater than or equal to 92.0%.

[0093] There is no particular upper limit to the degree of graphitization of graphite particles, as long as it is less than or equal to 100%. When the average particle size of graphite particles is large (for example, when it exceeds 12.0 μm), from the viewpoint that the hardness of graphite particles is sufficiently high and that they are not prone to particle deformation or damage, it can be less than or equal to 97.0%.

[0094] The degree of graphitization of graphite particles can be calculated, for example, as follows.

[0095] Ten or 20 parts by weight of silicon powder (e.g., NIST SRM640f) were mixed with a graphite sample in an agate mortar for 5 minutes. The resulting mixture was then placed in an X-ray diffraction specimen holder. Using an X-ray diffraction apparatus (e.g., Rigaku X-ray diffraction Analyzer MultiFlex), the diffraction angles corresponding to the (002) plane of graphite and the (111) plane of silicon were determined by X-ray diffraction of CuKα rays (2θ = 25°–29°).

[0096] The theoretical diffraction angle of Si (2θ = 28.441°) was used to correct the observed diffraction angles of silicon and graphite, thus determining the correct graphite diffraction angle.

[0097] The interplanar spacing of the d(002) plane of the negative electrode material was calculated using Bragg's formula (2dsinθ=nλ). The degree of graphitization is calculated using the following formula.

[0098] Degree of graphitization = [(3.44 - interplanar spacing) / (0.086)] × 100

[0099] (I 002 / I 110 )

[0100] Using the negative electrode material of this disclosure to form a negative electrode, from the viewpoint of the input characteristics of a lithium-ion secondary battery, the peak intensity (I) of the 002 diffraction line obtained by X-ray diffraction measurement of the negative electrode after it has been pressed at 0.8 t / cm using CuKα rays is analyzed. 002 The peak intensity of the 110 diffraction line (I) 110 The ratio of I to ) 002 / I 110 Preferably less than or equal to 350, more preferably less than or equal to 330, and even more preferably less than or equal to 300.

[0101] I 002 / I 110 There is no specific limit to the lower limit; it can be greater than or equal to 200.

[0102] I 002 / I 110 It can be determined using the methods described in the examples. Measurement I 002 / I 110 At that time, the components other than graphite particles and their ratios, which are conditions for manufacturing the negative electrode, and the manufacturing conditions of the negative electrode are the same as those described in the electrode orientation determination method of the embodiment.

[0103] (0-times tap density)

[0104] Considering the input-output characteristics and energy density of lithium-ion secondary batteries, as well as the ease of increasing compressive load, the preferred zero-tap density of graphite particles is 0.3 g / cm³. 3 ~0.6g / cm 3 More preferably 0.35 g / cm³ 3 ~0.55g / cm 3 .

[0105] The zero-order tap density of graphite particles is the density value calculated as follows: in a volume of 150 cm³... 3 100 cm³ of graphite particle sample powder was placed in a graduated flat-bottomed test tube (e.g., KRS-406, manufactured by Kurumichi Scientific Instruments Co., Ltd.). 3 The density value is determined from the mass and volume of the sample powder before the stoppered, graduated flat-bottomed test tube is dropped.

[0106] (30 tapped densities)

[0107] Considering the input-output characteristics and energy density of lithium-ion secondary batteries, as well as the ease of increasing compressive load, the preferred tap density of graphite particles after 30 vibrations is 0.4 g / cm³. 3 ~0.7g / cm 3 More preferably 0.45 g / cm³ 3~0.65g / cm 3 .

[0108] The 30th tap density of graphite particles can be calculated, for example, as follows.

[0109] 150cm 3 100 cm³ of graphite particle sample powder was placed in a graduated flat-bottomed test tube (e.g., KRS-406, manufactured by Kurumichi Scientific Instruments Co., Ltd.). 3 The graduated flat-bottomed test tube is then plugged. Next, the test tube is dropped from a height of 5 cm 30 times. The density value obtained from the mass and volume of the sample powder after 30 drops is taken as the 30-drop compaction density.

[0110] (250 tapped density)

[0111] Considering the input-output characteristics and energy density of lithium-ion secondary batteries, as well as the ease of increasing compressive load, the preferred tap density of graphite particles after 250 vibrations is 0.7 g / cm³. 3 ~1.1g / cm 3 More preferably 0.75 g / cm³ 3 ~1.0g / cm 3 .

[0112] The 250th vibrational tap density of graphite particles can be calculated, for example, as follows.

[0113] 150cm 3 100 cm³ of graphite particle sample powder was placed in a graduated flat-bottomed test tube (e.g., KRS-406, manufactured by Kurumichi Scientific Instruments Co., Ltd.). 3 Stopper the graduated flat-bottomed test tube. Then, drop the graduated flat-bottomed test tube from a height of 5 cm 250 times. Set the density value obtained from the mass and volume of the sample powder after 250 drops as the 250-drop compaction density.

[0114] (Specific surface area)

[0115] The specific surface area of ​​graphite particles, determined by nitrogen adsorption at 77 K, is not particularly limited. However, from the viewpoints of improving fast charge / discharge performance and suppressing electrolyte decomposition, a specific surface area of ​​0.2 m² is preferred for graphite particles. 2 / g~6.0m 2 / g, more preferably 1.5m 2 / g~5.0m 2 / g, further preferably 2.0m 2 / g~4.0m 2 / g.

[0116] The specific surface area determined by nitrogen adsorption at 77 K can be calculated using the BET method based on the adsorption isotherm obtained by nitrogen adsorption at 77 K. Specifically, the specific surface area can be calculated using the method described in the examples.

[0117] The specific surface area of ​​graphite particles can be adjusted by particle size distribution, particle structure, etc.

[0118] The specific surface area of ​​graphite particles can also be adjusted using coated graphite particles such as low-crystallinity carbon. When it is desired to reduce the particle size, the unevenness produced by crushing will cause the specific surface area to increase significantly. However, by coating, the unevenness can be filled in with the coating material to smooth it out, thereby adjusting the specific surface area.

[0119] Graphite particles can be treated with a low-crystallinity carbon coating on the surface, or the surface can be left untreated.

[0120] When the surface of graphite particles is coated with low-crystallinity carbon, there is a tendency for the charging characteristics at low temperatures to be further improved when constructing lithium-ion secondary batteries.

[0121] On the other hand, without coating the surface of the graphite particles with low-crystallinity carbon, it is possible to suppress cracking and peeling of the graphite particles during pressing in electrode fabrication, and to suppress the tendency for electrolyte decomposition activity to increase and storage properties to decrease. Furthermore, this offers the advantage of increased freedom in manufacturing conditions. Moreover, in the negative electrode material of this disclosure, even without low-crystallinity carbon on the surface, lithium metal deposition during charging can be suppressed.

[0122] If the value measured by Raman spectroscopy is at 1300 cm⁻¹ -1 ~1400cm -1 Peak intensity within the range (I) D ) and at 1580cm -1 ~1620cm -1 Peak intensity within the range (I) G The ratio of I to ) D / I G Let R be the value. The R value of graphite particles can be 0.10 to 0.40 or 0.10 to 0.35. In particular, it is preferred that the surface is not coated with low-crystallinity carbon and the R value is 0.10 to 0.40.

[0123] In this disclosure, the R value can be determined by the method described in the embodiments.

[0124] At 1300cm -1 ~1400cm -1 Peak intensity within the range (I)D The peak identified as corresponding to the amorphous structure of carbon is, for example, 1360 cm⁻¹. -1 A peak appeared nearby.

[0125] At 1580cm -1 ~1620cm -1 Peak intensity within the range (I) G The peak identified as corresponding to the crystal structure of graphite is, for example, 1580 cm⁻¹. -1 A peak appeared nearby.

[0126] When the surface of graphite particles is coated with low-crystallinity carbon, the above-mentioned R value can be 0.20 to 0.60 or 0.20 to 0.40.

[0127] (Rebound rate)

[0128] There is no particular limitation on the resilience of graphite particles. For example, from the viewpoint of further suppressing graphite particle damage caused by pressing during the production of the negative electrode, the resilience of graphite particles can be greater than or equal to 15%, or greater than or equal to 20%.

[0129] Considering the ease of achieving high density due to the pressing during the production of the negative electrode, the rebound rate of graphite particles can be less than or equal to 40%, or less than or equal to 35%.

[0130] In this disclosure, the resilience of graphite particles refers to the degree of density reduction when the pressure is released after the graphite particles have been compressed to a reference density. The greater the resilience, the easier it is for the graphite particles deformed by compression to return to their original state.

[0131] Specifically, a predetermined mass (e.g., 3.0 g) of graphite particles is filled into a mold and compressed at a constant rate (e.g., 10 mm / min) until the density of the graphite particles reaches a reference density (e.g., 1.7 g / cm³). 3 Then, the pressure is released, and the density after pressure release is measured when the pressed surface stops moving due to elasticity. The resilience is calculated from the obtained value using the following formula.

[0132] Rebound rate (%) = {(Reference density - Density after pressure release) / Reference density} × 100

[0133] In the above measurements, for example, a mold with a diameter of 15 mm was used as the mold, and compression was performed using Autograph (e.g., manufactured by Shimadzu Corporation). The density of the graphite particles was calculated based on the volume and mass of the graphite particles, wherein the volume of the graphite particles was determined by the bottom area of ​​the mold (e.g., 1.767 cm²). 2 The distance from the bottom of the mold to the pressing surface of the graphite particles is calculated.

[0134] The compressive load and resilience of graphite particles can be adjusted by changing the physical properties and composition of the raw materials (e.g., needle coke) or by changing the graphitization conditions.

[0135] In this disclosure, the average interplanar spacing (d) determined by X-ray diffraction will be used. 002 Carbon materials smaller than 0.340 nm are defined as graphite.

[0136] In this disclosure, as described below, particles in which at least a portion of the surface of a graphite particle is configured with low-crystallinity carbon are also referred to as "graphite particles".

[0137] The average interplanar spacing (d) of graphite crystals 002 The theoretical value of ) is 0.3354nm, and the closer it is to this value, the more graphitization has been carried out.

[0138] From the perspective of the initial charge-discharge efficiency and energy density of lithium-ion secondary batteries, the average interplanar spacing (d) 002 Preferably less than or equal to 0.33600 nm, more preferably less than or equal to 0.33596 nm, and even more preferably less than or equal to 0.33592 nm.

[0139] Considering the above viewpoints, the average interplanar spacing (d) of graphite particles 002 The preferred wavelength range is 0.3354nm to 0.33600nm, more preferably 0.3354nm to 0.33596nm, and even more preferably 0.3354nm to 0.33592nm.

[0140] The average interplanar spacing (d) of graphite particles 002 The average interplanar spacing (d) can be calculated as follows: Based on the diffraction peaks corresponding to the carbon 002 plane that appear near the diffraction angle 2θ of 24°–27° in the diffraction spectrum obtained by irradiating the sample with X-rays (CuKα rays) and measuring the diffraction lines using a goniometer, the average interplanar spacing (d) can be calculated using Bragg's formula. 002 The determination can be performed under the following conditions.

[0141] Radiation source: CuKα rays (wavelength = 0.15418 nm)

[0142] Output: 40kV, 20mA

[0143] Sampling width: 0.010°

[0144] Scanning range: 10°~35°

[0145] Scanning speed: 0.5° / min

[0146] Bragg's formula: 2dsinθ=nλ

[0147] Here, d represents the length of one period, θ represents the diffraction angle, n represents the number of reflections, and λ represents the X-ray wavelength.

[0148] The Particle Structure of Graphite Particles

[0149] Graphite particles can be a collection or combination of multiple graphite particles (preferably multiple flat graphite particles) (composite particles), or they can be composite particles with a structure formed by stacking multiple flat graphite particles (hereinafter also referred to as specific composite particles).

[0150] It is believed that certain composite particles, compared to composite particles with structures where the main faces of multiple flat graphite particles are oriented randomly, can reduce the contact area between the particles and the electrolyte, effectively suppressing electrolyte decomposition. Furthermore, it is believed that even under pressure during negative electrode fabrication, particle deformation or damage is less likely, ensuring electrolyte pathways between particles. In contrast, the electrolyte diffusion path within composite particles with structures where the main faces of multiple flat graphite particles are oriented randomly is complex and slow. Therefore, it is believed that even active materials with more particle interfaces may experience diffusion barriers, hindering high input / output performance. This tendency is particularly pronounced under high charge / discharge rate (C rate) input / output conditions.

[0151] The flat graphite particles contained in a specific composite particle refer to non-spherical graphite particles with anisotropic shapes. Examples of flat graphite particles include those with scaly, flake-like, and partially blocky shapes.

[0152] Composite particles are particles that are aggregated or combined with each other. Specifically, a particular composite particle has a structure formed by the superposition and aggregation of multiple flat graphite particles with their main faces facing each other. Therefore, multiple flat graphite particles superimposed in a roughly parallel state form a composite particle. Whether the flat graphite particles are stacked can be confirmed by microscopic observation.

[0153] The state of multiple flat graphite particles aggregated or combined refers to the state of two or more flat graphite particles aggregated or combined. Combination refers to the state in which particles are chemically bonded to each other directly or through carbon materials. Aggregation refers to the state in which particles are not chemically bonded to each other, but retain the shape of an aggregate due to their shape, etc.

[0154] Flat graphite particles can be aggregated or bonded together with carbonaceous materials in between. Examples of carbonaceous materials include graphite and carbides obtained by graphitizing binders such as tar, pitch, starch, PVA (polyvinyl alcohol), and CMC (carboxymethyl cellulose). From a mechanical strength perspective, a state in which two or more flat graphite particles are bonded together with carbonaceous materials in between is preferred. Whether the flat graphite particles are aggregated or bonded can be confirmed, for example, by observation using a scanning electron microscope.

[0155] To reduce the proportion of composite particles with structures where the main faces of multiple flat graphite particles face randomly, the amount of binder used should ideally be as small as possible. Composite particles are not generated without binder. On the other hand, if the binder is excessive, more primary particles are generated around the binder block, i.e., an aggregate intermediate containing multiple primary particles is created, and the primary particles in this intermediate tend to be in a non-parallel facing state.

[0156] To reduce lumps caused by the agglomeration of tar, pitch, etc., which act as binders, dispersants can also be used. By using dispersants, the binder is easily and uniformly dispersed, tending to reduce the amount of binder lumps. Therefore, it is believed that the proportion of composite particles with a structure in which the main faces of multiple flat graphite particles are oriented in a random direction can be reduced. Furthermore, the function of the binder is improved, the lump-forming property is enhanced, and the proportion of binder in the formulation can be reduced. Examples of dispersants that can be used in step (b) described later can be listed.

[0157] From the viewpoint of reducing the amount of adhesives such as asphalt used, aromatic compounds can also be used with adhesives. Examples of aromatic compounds that can be used in step (a) described later can be listed.

[0158] There are no particular limitations on the flat graphite particles and their raw materials, and examples include artificial graphite, flake natural graphite, flaky natural graphite, coke, and resin. Among these, artificial graphite, which is graphitized from coke, is preferred from the viewpoint of being less prone to deformation and having a low specific surface area. When natural graphite is used as a part of the raw material, it is easy to soften, so it is preferable to adjust the proportion while observing the compression load.

[0159] When graphite particles contain specific composite particles, all of the graphite particles can be specific composite particles, or some of them can be graphite particles other than specific composite particles.

[0160] [Second Implementation]

[0161] The negative electrode material for lithium-ion secondary batteries disclosed in the second embodiment of this invention is graphite particles such that, when a negative electrode material layer is formed using the negative electrode material for lithium-ion secondary batteries, the ratio of the tortuous path length L (μm) of the distance from one surface to another in the thickness direction through the voids inside the negative electrode material layer to the thickness T (μm) of the negative electrode material layer, i.e., L / T, satisfies less than or equal to 1.7.

[0162] In the negative electrode material for lithium-ion secondary batteries according to the second embodiment, by having an L / T ratio of less than or equal to 1.7, the distance that lithium ions travel from the surface of the negative electrode to the graphite particles deep within the negative electrode can be shortened. As a result, it can be deduced that the time difference between the charging reaction at the surface of the negative electrode and at its depth can be reduced, and lithium-ion secondary batteries with excellent lithium (Li) deposition resistance can be manufactured in the same manner as the negative electrode material of the first embodiment.

[0163] L / T can be determined as follows.

[0164] X-ray CT measurements were performed using a microfocus X-ray CT system SMX-160CTS (manufactured by Shimadzu Corporation) under the following conditions: tube voltage 48kV, SID axis 350mm, SOD axis 3mm, multiple cumulative scans 2, and slice spacing 0.001065mm. It should be noted that the electrodes were cut into 2mm × 15mm strips for measurement. Using the obtained CT images, 3D analysis was performed using EXFactVR and ExFact Analysis for Porous Particles (both manufactured by Visual Science Corporation, Japan). The minimum value of the tortuous path that passes through the voids inside the negative electrode material layer from the voids on the surface of the negative electrode material layer in the thickness direction to the surface of the electrolytic copper foil was determined, and its arithmetic mean was set as the tortuous path length L (μm). Then, the tortuosity was calculated by dividing the tortuous path length L by the thickness T (μm) of the negative electrode material layer. It should be noted that if multiple tortuous paths exist from a single gap on the surface of the electrolytic copper foil to the surface of the negative electrode material layer in the thickness direction, the value with the smallest tortuous path is selected. When measuring L / T, the components other than graphite particles and their ratios, which are conditions for manufacturing the negative electrode material layer, and the manufacturing conditions of the negative electrode material layer are the same as those described in the electrode orientation measurement method of the embodiment, except that no pressing process is performed.

[0165] In the negative electrode material for lithium-ion secondary batteries according to the second embodiment, L / T is preferably less than or equal to 1.65, and more preferably less than or equal to 1.6.

[0166] There is no special limitation on the lower limit of L / T as long as it is greater than or equal to 1.0. From the point of view of ease of manufacturing, it can be greater than or equal to 1.5.

[0167] The configuration described in the negative electrode material of the first embodiment and the configuration described in the negative electrode material for lithium-ion secondary batteries of the second embodiment can also be appropriately combined.

[0168] Manufacturing method of negative electrode material for lithium-ion secondary batteries

[0169] The method for manufacturing the negative electrode material for lithium-ion secondary batteries disclosed herein includes a step of graphitizing coke. More specifically, from the viewpoint of improving processability in graphitization and other processes, and improving the cycle characteristics of lithium-ion secondary batteries, the method for manufacturing the negative electrode material for lithium-ion secondary batteries disclosed herein preferably includes the following steps (a) to (d).

[0170] have:

[0171] (a) A process for obtaining a mixture comprising graphitizable aggregate (coke) and graphitizable binder.

[0172] (b) The above mixture is shaped to obtain a density less than or equal to 1.3 g / cm³. 3 The process of forming the product,

[0173] (c) The process of graphitizing the above-mentioned molded article to obtain a graphitized article, and

[0174] (d) The process of pulverizing the above-mentioned graphitized material to obtain pulverized material.

[0175] It should be noted that the steps in the above method can be performed continuously or discontinuously. The steps can be performed in the same location or in different locations.

[0176] There are no particular restrictions on the type of coke used in the above manufacturing method. Examples include fluidized coke, needle coke, embedded coke, and semi-needle coke, which has intermediate properties between needle coke and embedded coke, as well as other petroleum-based or coal-based cokes.

[0177] There are no particular restrictions on the method for obtaining coke particles (coke particles), and it can be implemented using known methods. There are no particular restrictions on the particle size of the coke particles; it can be selected considering the desired particle size and particle structure of the graphite particles. To obtain particles with a lower specific surface area, it is preferable to pulverize them in the state of raw coke. Such particles have fewer voids and cracks caused by splitting, and tend to have a higher compressive load on the graphite particles.

[0178] In the manufacturing method disclosed herein, after obtaining a mixture comprising graphitizable aggregate and graphitizable binder, the mixture is shaped to obtain a density less than or equal to 1.3 g / cm³. 3The molded article. In the manufacturing method disclosed herein, a mixture containing aromatic compounds may also be used as the mixture for forming the molded article. As a result, the appearance of the molded article is improved, the strength of the molded article is further increased, and thus the processability in subsequent graphitization processes is also improved.

[0179] The following reasoning can be inferred as to why the appearance of the molded article is improved and the strength of the molded article is further enhanced by using a mixture containing aromatic compounds as the mixture for forming the molded article.

[0180] (1) By adding a liquid containing an aromatic compound to a mixture containing graphitizable aggregate, the surface of the graphitizable aggregate becomes easier to slide during the molding of the mixture, promoting the alignment of the mixture and reducing voids. (2) The graphitizable binder is dissolved in the mixture, resulting in a highly uniform dispersion of the binder. It is believed that through the above (1) and (2), the appearance of the molded article is improved, and the strength of the molded article is also increased.

[0181] Furthermore, in the manufacturing method of this disclosure, after obtaining a molded article with low density, the molded article is graphitized, and then the graphitized article is pulverized, thereby tending to manufacture lithium-ion secondary batteries with excellent cycle characteristics. The reason for this is as follows: In the manufacturing method of this disclosure, compared to pulverizing graphitized articles obtained using a molded article with high density, the graphitized article can be easily pulverized, resulting in pulverized articles with a small specific surface area. By using the negative electrode material containing pulverized articles with a small specific surface area in the manufacture of lithium-ion secondary batteries, the contact area between the negative electrode material and the electrolyte can be reduced. This suppresses electrolyte decomposition reactions and extends battery life, resulting in excellent cycle characteristics of the lithium-ion secondary battery.

[0182] In step (a), a mixture comprising graphitizable aggregate, graphitizable binder, and an aromatic compound as needed is obtained. Mixing is preferably carried out at a temperature at which the graphitizable binder softens. Specifically, this can be 50°C to 300°C when the graphitizable binder is pitch, tar, etc., and 20°C to 100°C when it is a thermosetting resin.

[0183] There are no particular restrictions on the mixing method. For example, it is preferable to use a planetary mixer, an impact mixer, or a paddle mixer. A kneading machine, also known as a mixing machine, can also be used.

[0184] When the graphitizable aggregate is in the form of particles, the average particle size (D50) of the graphitizable aggregate is preferably 5 μm to 40 μm, more preferably 10 μm to 30 μm, and even more preferably 10 μm to 25 μm.

[0185] The standard deviation of the particle size distribution of the graphitizable aggregate is preferably less than or equal to 0.35, more preferably less than or equal to 0.20, even more preferably less than or equal to 0.18, and particularly preferably less than or equal to 0.16. By ensuring the standard deviation of the aggregate particle size distribution is less than or equal to 0.35, the particle size deviation of the aggregate can be reduced, and the particle size deviation of the obtained pulverized material can be suppressed. By using a negative electrode material containing pulverized material with small particle size deviation in the manufacture of lithium-ion secondary batteries, the resistance distribution within the negative electrode can be made more uniform. As a result, there is a tendency to improve the fast-charging performance of the lithium-ion secondary battery. Furthermore, by reducing the particle size deviation of the aggregate, even if the content or percentage of the graphitizable binder is reduced, its function as a binder can be adequately ensured. The standard deviation of the particle size distribution is, for example, a value determined by laser diffraction (volume basis).

[0186] There is no particular limit to the lower limit of the standard deviation of the particle size distribution of graphitizable aggregates; for example, it can be greater than or equal to 0.05 or greater than or equal to 0.10.

[0187] Methods for adjusting the average particle size and standard deviation of the particle size distribution of graphitizable aggregates to the aforementioned range include grading using sieves, air grading, and wet grading.

[0188] There are no particular restrictions on graphitizable adhesives, as long as they are graphitized through a graphitization process. Specifically, examples include coal-based, petroleum-based, and synthetic asphalt and tar, starch, PVA, CMC, thermoplastic resins, and thermosetting resins.

[0189] The graphitizable aggregate and graphitizable binder contained in the mixture may be one or more.

[0190] When starch is used as a binder, it becomes a hard carbide compared to when coal tar pitch is used, tending to increase the compressive load on graphite particles. Therefore, based on equation (1), there is a tendency to improve the input characteristics of lithium-ion secondary batteries, such as Li precipitation resistance. When starch is used, there is a tendency to improve the formability of the mixture, thus allowing for a smaller amount of binder. As a result, the coke ratio in the mixture increases, tending to increase the discharge capacity of the lithium-ion secondary battery.

[0191] There are no particular limitations on the content of each material in the mixture. For example, the content of the graphitizable binder relative to 100 parts by weight of the graphitizable aggregate can be 10 to 30 parts by weight, 12 to 25 parts by weight, or 14 to 20 parts by weight. When the above-mentioned binder is added to a solvent or dispersion medium and used as a solution or dispersion, the mass of the solvent or dispersion medium is not included. If the binder content is greater than or equal to 10 parts by weight, there is a tendency for it to function as a binder suitable for graphitizable aggregate. If the binder content is less than or equal to 30 parts by weight, the fixed carbon content in the mixture can be sufficiently ensured, and there is a tendency for excellent yield.

[0192] The graphitizable aggregate and graphitizable binder contained in the mixture may be one or more.

[0193] There are no particular limitations on aromatic compounds as long as they contain an aromatic ring. An aromatic compound can be a compound with an aromatic ring and a molecular weight of 500 or less, or a compound with a molecular weight of 300 or less.

[0194] As aromatic compounds, examples include naphthalene, 1-methylnaphthalene, 2-methylnaphthalene, methylnaphthalene, acenaphthene, biphenyl, fluorene, benzo[a]pyrene, benzo[a]anthracene, dibenzo[a]anthracene, dibenzo[a]furan, quinoline, isoquinoline, etc.

[0195] The mixture may contain only one or more aromatic compounds.

[0196] Among these, methylnaphthalene and naphthalene are preferred as aromatic compounds from the viewpoint of formability when forming the molded article.

[0197] When the mixture contains aromatic compounds, the content of aromatic compounds in the mixture relative to 100% by mass of the aggregate and binder is preferably 1% to 20% by mass, more preferably 2% to 18% by mass, and even more preferably 3% to 15% by mass.

[0198] The mixture may also contain other components besides graphitizable aggregates, graphitizable binders, and aromatic compounds. Examples of other components include graphite, dispersants, and graphitization catalysts.

[0199] The mixture may also contain graphite. Examples of graphite include natural graphite and synthetic graphite. Graphite is preferably in particulate form. The mixture may contain only one type of graphite or may contain two or more types of graphite.

[0200] From the viewpoint that the components in the mixture can be easily dispersed in step (b) described later, the mixture preferably contains a dispersant. By containing a dispersant in the mixture, particle size deviation of the pulverized material obtained by pulverizing graphitized material can be suppressed, and pulverized material with uniform particle size can be easily obtained. As a result, there is a tendency to improve the fast charging performance of lithium-ion secondary batteries.

[0201] Furthermore, the presence of a dispersant in the mixture is related to the amount of graphitizable binder that inhibits its use, which can also lead to improvements in battery characteristics such as the initial charge-discharge efficiency of the negative electrode material.

[0202] There are no particular restrictions on the type of dispersant. Specifically, examples include hydrocarbons such as liquid paraffin, paraffin wax, and polyethylene wax; fatty acids such as stearic acid, oleic acid, erucic acid, and 12-hydroxystearic acid; fatty acid metal salts such as zinc stearate, lead stearate, aluminum stearate, calcium stearate, and magnesium stearate; fatty acid amides such as stearamide, oleamide, erucamide, methylene bis-stearamide, and ethylene bis-stearamide; fatty acid esters such as monoglyceride stearate, stearate stearate, and hardened oil; and higher alcohols such as stearyl alcohol. Among these, fatty acids are preferred because they are less likely to affect the performance of the negative electrode material, are easy to handle because they are solid at room temperature, are uniformly dispersed because they melt at the temperature of step (a), disappear during the process until graphitization, and are inexpensive.

[0203] When the mixture contains a dispersant, there is no particular limitation on its amount. For example, the content of the dispersant relative to the total mixture can be 0.1% to 20% by mass, 0.5% to 10% by mass, or 0.5% to 5% by mass.

[0204] From the viewpoint of promoting the graphitization of graphitizable aggregates or binders, the mixture preferably contains a graphitization catalyst. There are no particular limitations on the type of graphitization catalyst. Specifically, examples include substances that have graphitization catalytic activity such as silicon, iron, nickel, titanium, and boron, as well as carbides, oxides, and nitrides of these substances.

[0205] When the mixture contains a graphitization catalyst, there is no particular limitation on its amount. For example, the content of the graphitization catalyst relative to the total mixture can be 0.1% to 50% by mass, 0.5% to 40% by mass, or 0.5% to 30% by mass.

[0206] In step (b), the mixture obtained in step (a) is shaped to obtain a molded article. It is preferable to use a uniaxial press or the like to shape it into a predetermined shape. By shaping in this way, when the mixture is graphitized, the filling amount in the graphitization furnace can be increased to improve productivity or the effect of the graphitization catalyst can be improved.

[0207] In process (b), there are no particular restrictions on the method of forming the mixture. Examples include: molding, in which the mixture is placed in a container such as a mold and pressure is applied in a uniaxial direction; vibration forming, in which the mixture is added to a container such as a mold, a weight is placed on it, and vibration and impact are applied to a metal frame to form the mixture; and extrusion forming, in which the mixture is extruded from a nozzle or the like through a horizontal extruder.

[0208] In step (b), the density of the obtained molded article must be less than or equal to 1.3 g / cm³. 3 Therefore, considering both the productivity of the negative electrode material and the cycle characteristics of the lithium-ion secondary battery, a concentration of 0.8 g / cm³ is preferred. 3 ~1.3g / cm 3 More preferably 1.0 g / cm³ 3 ~1.25g / cm 3 Further preferred value is 1.05 g / cm³. 3 ~1.2g / cm 3 Therefore, after obtaining a molded material with a low density, the molded material can be graphitized, and then the graphitized material can be pulverized. Thus, compared to pulverizing graphitized materials obtained using a molded material with a high density, the graphitized material can be pulverized more easily. As a result, there is a tendency to obtain pulverized materials with a small specific surface area. By using a negative electrode material containing pulverized materials with a small specific surface area in the manufacture of lithium-ion secondary batteries, the contact area between the negative electrode material and the electrolyte can be reduced. Therefore, the decomposition reaction of the electrolyte can be suppressed, extending battery life, and there is a tendency to manufacture lithium-ion secondary batteries with excellent cycle characteristics.

[0209] As mentioned above, reducing the density of graphitized molded materials is considered advantageous in improving the performance of lithium-ion secondary batteries. For example, by reducing the fixed carbon from the binder, there is a tendency to adjust the density of graphitized molded materials to a low level. From the viewpoint of reducing the density of graphitized molded materials, binders with low fixed carbon content and exhibiting adhesiveness, such as corn starch, tapioca starch, PVA, and CMC, are suitable for use.

[0210] The fixed carbon content of the graphitizable binder in the mixture is preferably less than or equal to 20% by mass relative to 100% by mass of the aggregate and binder (before graphitization), more preferably less than or equal to 15% by mass, further preferably less than or equal to 10% by mass, and particularly preferably less than or equal to 5% by mass. The lower the fixed carbon content of the graphitizable binder in the mixture, the higher the coke ratio in the mixture, and the greater the tendency for the discharge capacity of the lithium-ion secondary battery to increase.

[0211] There is no particular limitation on the lower limit of the fixed carbon content of the graphitizable binder in the mixture, which can be greater than or equal to 0.5% by mass or greater than or equal to 1.0% by mass relative to 100% mass of aggregate and binder (before graphitization).

[0212] The molded article obtained in step (b) is preferably heat-treated before graphitization in step (c). By performing heat treatment, organic components in the mixture that do not contribute to graphitization are removed, and there is a tendency to suppress gas generation during graphitization.

[0213] There are no particular limitations on the temperature of the heat treatment described above, but it is preferably a temperature lower than the heat treatment temperature in step (c). For example, it can be carried out in the range of 500°C to 1000°C.

[0214] In step (c), the molded article obtained in step (b) is graphitized. There are no particular restrictions on the method for graphitizing the molded article, as long as the conditions allow for the graphitization of the graphitizable components contained in the mixture. For example, methods involving heat treatment in an atmosphere where the mixture is not easily oxidized can be listed. There are no particular restrictions on the atmosphere where the mixture is not easily oxidized; examples include inactive atmospheres such as nitrogen and argon, and vacuum.

[0215] The heat treatment temperature for graphitization can be, for example, greater than or equal to 1500°C, greater than or equal to 2000°C, greater than or equal to 2500°C, or greater than or equal to 2800°C. There is no particular upper limit to the heat treatment temperature; for example, it can be less than or equal to 3200°C. If the heat treatment temperature is greater than or equal to 1500°C, there is a tendency for crystallization changes to occur, making graphitization easier. If the heat treatment temperature is greater than or equal to 2000°C, there is a tendency for graphite crystal growth to become more favorable. On the other hand, if the heat treatment temperature for graphitization is less than or equal to 3200°C, there is a tendency for some of the graphite to sublimate.

[0216] In step (d), the graphitization obtained in step (c) is pulverized to obtain pulverized material. There are no particular limitations on the pulverization method; jet mills, vibratory mills, pin mills, hammer mills, etc., and other known methods can be used. The particle size of the pulverized material can also be adjusted to achieve the desired size. There are no particular limitations on the method for adjusting the particle size; methods using the aforementioned pulverizing apparatus, methods using sieves, etc., are examples.

[0217] If necessary, the pulverized material obtained in step (d) may also be subjected to step (e) of configuring low-crystallinity carbon on at least a portion of the surface of the pulverized material; or step (f) of mixing the pulverized material with other negative electrode active materials.

[0218] In step (e), as a method for distributing low-crystallinity carbon on at least a portion of the surface of the pulverized material, a method can be listed as mixing a substance (such as resin) that can become low-crystallinity carbon through heat treatment with the pulverized material and then performing heat treatment. If low-crystallinity carbon is distributed on at least a portion of the surface of the pulverized material, the input-output characteristics, such as the fast charge-discharge characteristics, of lithium-ion secondary batteries that use it as a negative electrode material are sometimes improved.

[0219] [Other processes]

[0220] The method for manufacturing the negative electrode material disclosed herein may also include steps other than those described above.

[0221] For example, the manufacturing method of the negative electrode material can also include a step of attaching an organic compound to the surface of secondary particles after graphitization and then performing heat treatment. By attaching the organic compound to the surface of the secondary particles and performing heat treatment, the organic compound attached to the surface is transformed into low-crystallinity carbon. Thus, it is possible to perform a treatment to coat the surface of the graphite particles with low-crystallinity carbon.

[0222] There are no particular limitations on the methods for attaching organic compounds to the surface of secondary particles. Examples include wet methods where secondary particles are dispersed and mixed in a mixed solution obtained by dissolving or dispersing the organic compound in a solvent, and then the solvent is removed to allow attachment; and dry methods where mechanical energy is applied to a mixture of secondary particles and a solid organic compound to allow attachment.

[0223] There are no particular restrictions on the organic compounds that can be transformed into low-crystallinity carbon (carbon precursors) through heat treatment. Examples include petroleum-based asphalt, naphthalene, anthracene, phenanthroline, coal tar, phenolic resins, and polyvinyl alcohol. Organic compounds can be used alone or in combination with two or more.

[0224] When heat-treating secondary particles with organic compounds adhering to their surface, there is no particular limitation on the heat treatment temperature, as long as the organic compounds adhering to the surface of the secondary particles change into low-crystallinity carbon. For example, 400°C to 1500°C is preferred. From the viewpoint of particularly improving high-temperature resistance, 1000°C to 1500°C is more preferred. The heat treatment is preferably carried out in an inert gas atmosphere, such as nitrogen.

[0225] In step (f), there are no particular limitations on the method of mixing the pulverized material with other negative electrode active materials. By mixing the pulverized material with other negative electrode active materials, the desired characteristics of the lithium-ion secondary battery can sometimes be improved compared to using the pulverized material alone as the negative electrode active material. Examples of other negative electrode active materials include graphite particles such as natural graphite and artificial graphite, and particles containing elements capable of absorbing and releasing lithium ions, but are not limited to these. There are no particular limitations on the elements capable of absorbing and releasing lithium ions; examples include Si, Sn, Ge, In, etc.

[0226] The pulverized material obtained in step (f) may contain particles that are aggregated or combined with multiple flat graphite particles, or particles that are aggregated or combined with multiple flat graphite particles in such a way that the main faces of the graphite particles are not parallel to each other (hereinafter also referred to as secondary graphite particles).

[0227] If the pulverized material is in the state of secondary graphite particles, then during the high-density pressing for the negative electrode, the phenomenon of the particles of the negative electrode material oriented along the direction of the current collector is suppressed, and there is a tendency to ensure the path of lithium ions entering and leaving the negative electrode material.

[0228] Furthermore, by using particles that comprise a collection or combination of multiple flat graphite particles, the impact of the pressure applied during compression on each graphite particle, caused by the voids existing between the multiple flat graphite particles, can be reduced, and there is a tendency to suppress graphite particle damage and cracking. As a result, there is a tendency for increased compressive load on graphite particles and excellent resistance to Li precipitation.

[0229] In this disclosure, "flat graphite particles" refers to non-spherical graphite particles with anisotropic shapes. Examples of flat graphite particles include those with scaly, flake-like, or partially blocky shapes.

[0230] Regarding flat graphite particles, when the length along the major axis is denoted as A and the length along the minor axis is denoted as B, the aspect ratio expressed as A / B is preferably 1.2 to 20, more preferably 1.3 to 10. If the aspect ratio is greater than or equal to 1.2, there is a tendency for the contact area between particles to increase, and the conductivity to be further improved. If the aspect ratio is less than or equal to 20, there is a tendency for the input and output characteristics of lithium-ion secondary batteries, such as the fast charge and discharge characteristics, to be further improved.

[0231] Aspect ratio is determined by observing graphite particles under a microscope. One hundred graphite particles are randomly selected, and their A / B ratios are measured. The arithmetic mean of these measurements is taken. When observing the aspect ratio, the length A along the major axis and the length B along the minor axis are measured as follows: In the projected image of the graphite particles observed under the microscope, the tangent a1 and a2, which are parallel to and tangent to the outer periphery of the graphite particle, are selected. The distance between these two tangents is defined as the length A along the major axis. Similarly, the tangent b1 and b2, which are parallel to and tangent to the outer periphery of the graphite particle, are selected. The distance between these two tangents is defined as the length B along the minor axis.

[0232] In this disclosure, "non-parallel principal faces" of graphite secondary particles refers to the fact that the largest cross-sectional area (principal face) of multiple flat graphite particles is not aligned in a certain direction. Whether the principal faces of multiple flat graphite particles are non-parallel can be confirmed by microscopic observation. By assembling or combining multiple flat graphite particles with their principal faces non-parallel, the increased principal face orientation of the flat graphite particles in the negative electrode can be suppressed, the negative electrode expansion accompanying charging can be suppressed, and there is a tendency to further improve the cycle characteristics of lithium-ion secondary batteries.

[0233] It should be noted that graphite secondary particles can also partially include structures in which multiple flat graphite particles are aggregated or combined in a manner where their principal faces are parallel.

[0234] From the viewpoint of ease of aggregation or combination, the average particle size of the flat graphite particles is preferably 1 μm to 50 μm, more preferably 1 μm to 25 μm, and even more preferably 1 μm to 15 μm. As a method for determining the average particle size of the flat graphite particles, a method using a scanning electron microscope can be cited, where the average particle size is, for example, the arithmetic mean of the particle sizes of 100 flat graphite particles.

[0235] There are no particular restrictions on flat graphite particles and their raw materials, including artificial graphite, flake natural graphite, flaky natural graphite, coke, resin, tar, and pitch. Among these, artificial graphite, natural graphite, or graphite obtained from coke, due to their high crystallinity and soft particle size, tend to be easier to achieve high density in the negative electrode.

[0236] The negative electrode material can also contain spherical graphite particles. When the negative electrode material contains spherical graphite particles, since the spherical graphite particles themselves are high-density, there is a tendency to reduce the pressing pressure required to obtain the desired electrode density.

[0237] Examples of spherical graphite particles include spherical synthetic graphite and spherical natural graphite. From the viewpoint of achieving high density in the negative electrode, spherical graphite particles are preferably high-density graphite particles. Specifically, spherical natural graphite, which can achieve high tap density through particle spheroidization treatment, is preferred. Furthermore, the negative electrode material layer containing spherical natural graphite exhibits excellent peel strength and tends to be difficult to peel off from the current collector even under strong pressure.

[0238] When the negative electrode material contains spherical graphite particles, it may also contain the aforementioned flat graphite particles and spherical graphite particles. When the negative electrode material contains the aforementioned flat graphite particles and spherical graphite particles, there is no particular limitation on the ratio of the two, and it can be set according to the desired electrode density, the pressure conditions during pressing, the desired battery characteristics, etc.

[0239] When a negative electrode material contains both flat and spherical graphite particles, examples include a mixture of flat and spherical graphite particles, and a combination of flat and spherical graphite particles (hereinafter also referred to as flat-spherical composite particles). For example, a flat-spherical composite particle can be a particle in which flat and spherical graphite particles are combined through a carbide of organic matter.

[0240] The aforementioned flat-spherical composite particles can be manufactured, for example, by using a mixture containing flat graphite particles or their raw materials and spherical graphite particles as the mixture in step (a).

[0241] Anode Material Composition for Lithium-ion Secondary Batteries

[0242] The lithium-ion secondary battery negative electrode material composition disclosed herein comprises the lithium-ion secondary battery negative electrode material of this disclosure, a binder, and a solvent. The lithium-ion secondary battery negative electrode material composition disclosed herein can be a slurry formed by mixing the lithium-ion secondary battery negative electrode material, the binder, and the solvent together.

[0243] Mixing can be carried out using dispersing devices such as dispersion mixers and planetary mixers.

[0244] There are no particular limitations on the binder used in the preparation of the negative electrode material composition for lithium-ion secondary batteries. Examples of binders include styrene-butadiene copolymer (SBR), methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, etc., as well as homopolymers or copolymers of ethylene unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, polyvinylidene fluoride, polyethylene oxide, polyepoxychlorohydrin, polyphosphazene, polyacrylonitrile, polymethacrylonitrile, etc., which are polymers with high ion conductivity. When the negative electrode material composition for lithium-ion secondary batteries includes a binder, the binder content is not particularly limited. For example, it can be 0.5 parts by weight to 20 parts by weight relative to 100 parts by weight of the total negative electrode material and binder for lithium-ion secondary batteries.

[0245] The negative electrode material composition for lithium-ion secondary batteries may also contain a thickener. As a thickener, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid or its salts, oxidized starch, phosphorylated starch, casein, etc., can be used. When the negative electrode material composition for lithium-ion secondary batteries contains a thickener, the content of the thickener is not particularly limited. For example, it can be 0.1 parts by weight to 5 parts by weight relative to 100 parts by weight of the negative electrode material for lithium-ion secondary batteries.

[0246] The negative electrode material composition for lithium-ion secondary batteries may include conductive auxiliary materials. Examples of conductive auxiliary materials include carbon materials such as carbon black, graphite, and acetylene black, as well as inorganic compounds such as oxides and nitrides that exhibit conductivity. When the negative electrode material composition for lithium-ion secondary batteries includes conductive auxiliary materials, the content of the conductive auxiliary materials is not particularly limited. For example, it may be 0.5 to 15 parts by weight relative to 100 parts by weight of the negative electrode material for lithium-ion secondary batteries.

[0247] Negative electrode for lithium-ion secondary batteries

[0248] The negative electrode for lithium-ion secondary batteries disclosed herein comprises a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for lithium-ion secondary batteries disclosed herein. In addition to the negative electrode material layer and current collector comprising the negative electrode material for lithium-ion secondary batteries disclosed herein, the negative electrode for lithium-ion secondary batteries may also include other constituent elements as needed.

[0249] The negative electrode for a lithium-ion secondary battery can be manufactured, for example, by: preparing the negative electrode material composition for a lithium-ion secondary battery disclosed above, coating it onto a current collector to form a negative electrode material layer; or by shaping the negative electrode material composition for a lithium-ion secondary battery into a sheet, granules, or other shape, and integrating it with a current collector.

[0250] There are no particular restrictions on the material of the current collector; it can be selected from aluminum, copper, nickel, titanium, stainless steel, etc. There are also no particular restrictions on the state of the current collector; it can be selected from foil, perforated foil, mesh, etc. In addition, porous materials such as porous metals (foamed metals) and carbon paper can also be used as current collectors.

[0251] When coating a negative electrode material composition for lithium-ion secondary batteries onto a current collector to form a negative electrode material layer, there are no particular limitations on the method. Known methods such as metal mask printing, electrostatic coating, dip coating, spraying, roller coating, doctor blade coating, corner wheel coating, gravure coating, and screen printing can be used. After coating the negative electrode material composition onto the current collector, the solvent contained in the composition is removed by drying. Drying can be performed using, for example, a hot air dryer, an infrared dryer, or a combination of these devices. The negative electrode material layer can also be calendered as needed. Calendering can be performed using a flatbed press, calendering rollers, or similar methods.

[0252] When integrating a lithium-ion secondary battery negative electrode material composition, formed into the shape of sheets or granules, with a current collector to form a negative electrode material layer, the integration method is not particularly limited. For example, it can be carried out by a roller, a flatbed press, or a combination of these methods. The pressure when integrating the lithium-ion secondary battery negative electrode material composition with the current collector is preferably, for example, in the range of 1 MPa to 200 MPa.

[0253] There are no particular limitations on the negative electrode density of the negative electrode material layer; for example, a density of 1.1 g / cm³ is preferred. 3 ~1.8g / cm 3 More preferably 1.1 g / cm³ 3 ~1.7g / cm 3 Further preferred value is 1.1 g / cm³. 3 ~1.6g / cm 3 By setting the negative electrode density to be greater than or equal to 1.1 g / cm³ 3 This results in a tendency to suppress the increase in resistance and increase the capacitance, which can be achieved by setting it to be less than or equal to 1.8 g / cm³. 3 This leads to a tendency to suppress the reduction in input characteristics and loop characteristics.

[0254] Lithium-ion secondary batteries

[0255] The lithium-ion secondary battery disclosed herein includes a negative electrode, a positive electrode, and an electrolyte for use in lithium-ion secondary batteries.

[0256] Similar to the method for manufacturing the negative electrode described above, the positive electrode can be obtained by forming a layer of positive electrode material on the current collector. As the current collector, a current collector made of metals or alloys such as aluminum, titanium, and stainless steel in the form of foil, perforated foil, or mesh can be used.

[0257] There are no particular limitations on the cathode material used to form the cathode material layer. Examples of cathode materials include metal compounds (metal oxides, metal sulfides, etc.) and conductive polymer materials capable of doping or inserting lithium ions. More specifically, examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCo... x Ni y Mn z O2, x+y+z=1), and composite oxides containing added element M' (LiCo) a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel-type lithium manganese oxide (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 The cathode material can be a single metal compound or a combination of two or more materials, including: VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, and polybenzoxene, and porous carbon.

[0258] There are no particular restrictions on the electrolyte; for example, an electrolyte made by dissolving lithium salt, which serves as the electrolyte, in a non-aqueous solvent (so-called organic electrolyte) can be used.

[0259] Examples of lithium salts include LiClO4, LiPF6, LiAsF6, LiBF4, and LiSO3CF3. A lithium salt can be a single type or two or more.

[0260] Examples of non-aqueous solvents include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butyl carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propanesulfonate lactone, 3-methylsulfolane, 2,4-dimethylsulfolane, and 3-methyl-1,3- The solvents include 2-oxazolidinone, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, triethyl phosphate, etc. Non-aqueous solvents can be a single solvent or two or more.

[0261] The state of the positive and negative electrodes in a lithium-ion secondary battery is not particularly limited. For example, the positive and negative electrodes, along with the separator configured between them as needed, can be wound into a vortex shape, or they can be stacked in a flat plate shape.

[0262] There are no particular limitations on the separator; for example, it can be made of resin-based nonwoven fabric, cloth, microporous membrane, or a combination thereof. Examples of resins include those primarily composed of polyolefins such as polyethylene and polypropylene. In lithium-ion secondary batteries where the positive and negative electrodes are not in contact, a separator may not be necessary.

[0263] There are no particular restrictions on the shape of lithium-ion secondary batteries. Examples include laminated batteries, paper batteries, button batteries, coin-shaped batteries, stacked batteries, cylindrical batteries, and prismatic batteries.

[0264] The lithium-ion secondary battery disclosed herein is suitable as a high-capacity lithium-ion secondary battery for use in electric vehicles, power tools, energy storage devices, etc.

[0265] Example

[0266] The present disclosure is described in detail below through embodiments, but the present disclosure is not limited to these embodiments.

[0267] [Example 1]

[0268] As a raw material for graphite particles, raw coke (needle coke) derived from petroleum is used.

[0269] The raw coke was coarsely crushed using a hammer mill. The coarsely crushed material was sieved using a 3mm sieve, and the sieved material was sieved using a 1mm sieve, thereby recovering particles with a diameter of 1mm to 3mm.

[0270] The obtained coke particles were pulverized and classified using a roller mill to obtain flat coke particles with a D50 of 9 μm. The standard deviation (σ) of the particle size distribution of the coke particles was 0.14.

[0271] The obtained coke particles (85 parts by mass), coal tar pitch (softening point 80℃~130℃, quinoline insoluble content less than or equal to 15% by mass, fixed carbon 50% by mass, denoted as "Pitch 1" in Table 1) and methylnaphthalene (an aromatic compound, 15 parts by mass relative to the total 100 parts by mass of the coke particles and coal tar pitch) were kneaded using a kneader to obtain a mixture.

[0272] Next, the obtained mixture was pressed at room temperature using a uniaxial press to a density less than or equal to 1.3 g / cm³. 3 A molded article was obtained. Next, the molded article was heat-treated at 850°C for 8 hours in a nitrogen atmosphere, followed by graphitization at 3000°C for 30 hours. The obtained graphitized article was pulverized to obtain particles. Then, the obtained particles were sieved through a 280-mesh screen to obtain graphite particles for use as a negative electrode material. The volumetric particle size distribution of the graphite particles was determined using a laser diffraction particle size distribution measuring device (SALD3100, Shimadzu Corporation). The results were: D10 = 5.5 μm, D50 = 10.0 μm, D90 = 25.5 μm, and D99.9 = 69.9 μm. The standard deviation (σ) of the graphite particle size distribution was 0.26.

[0273] [Example 2]

[0274] In Example 1, coke particles and coal tar pitch were stirred and mixed using a mixer instead of kneading using a kneader. Otherwise, the same procedure as in Example 1 was followed to obtain graphite particles as the negative electrode material.

[0275] The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite particles. The results are shown in Table 1.

[0276] [Example 3]

[0277] The coal tar pitch (softening point 80℃~130℃, quinoline insoluble content less than or equal to 15% by mass, fixed carbon 50% by mass, denoted as "Pitch 1" in Table 1) used in Example 1 was replaced with coal tar pitch (softening point 220℃~280℃, quinoline insoluble content less than or equal to 20% by mass, fixed carbon 70% by mass, denoted as "Pitch 2" in Table 1). Otherwise, the procedure was the same as in Example 1 to obtain graphite particles as the negative electrode material.

[0278] The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite particles. The results are shown in Table 1.

[0279] [Examples 4-6]

[0280] In Examples 1-3, coke particles with a D50 of 5 μm and a standard deviation (σ) of 0.16 in particle size distribution were used to produce graphite particles. Otherwise, the same procedures were followed as in Examples 1-3 to obtain graphite particles as negative electrode materials.

[0281] The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite particles. The results are shown in Table 1.

[0282] [Example 7]

[0283] The graphite particles prepared in Example 1 were prepared by treating coal tar pitch (“pitch 2” in Table 1) under the following conditions to produce graphite particles with a surface coating of low-crystallinity carbon (hereinafter also referred to as “coated graphite particles”).

[0284] 100 parts by mass of graphite particles prepared in Example 1 and 4 parts by mass of coal tar pitch were mixed. The resulting mixture was then heated to 1200°C at a rate of 200°C / hour under nitrogen atmosphere and held at 1200°C (the calcination temperature) for 2 hours. The calcined graphite particles were then pulverized using a shredder and sieved through a 280-mesh sieve to obtain the coated graphite particles that passed through the sieve, which were used as the negative electrode material.

[0285] The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the coated graphite particles. The results are shown in Table 1.

[0286] [Example 8]

[0287] For the graphite particles prepared in Example 6, coal tar pitch (“Pitch 2” in Table 1) was treated under the same conditions as in Example 7 to prepare coated graphite particles.

[0288] The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the coated graphite particles. The results are shown in Table 1.

[0289] [Example 9]

[0290] Using a mixer, 85 parts by mass of coke particles with a D50 of 9 μm, 25 parts by mass of coal tar pitch, and 10 parts by mass of starch (fixed carbon 10% by mass) used in Example 1 were stirred and mixed to obtain a mixture.

[0291] Next, the obtained mixture was pressed at room temperature using a uniaxial press to a density less than or equal to 1.3 g / cm³. 3A molded article was obtained. Next, the molded article was heat-treated at 850°C for 8 hours in a nitrogen atmosphere, followed by graphitization at 3000°C for 30 hours. The obtained graphitized article was pulverized to obtain particles. Then, the obtained particles were sieved through a 280-mesh screen to obtain graphite particles for use as the negative electrode material. The volumetric particle size distribution of the graphite particles was determined using a laser diffraction particle size distribution measuring device (SALD3100, Shimadzu Corporation). The results were: D10 = 6.7 μm, D50 = 12.7 μm, D90 = 27.9 μm, and D99.9 = 68.8 μm. The standard deviation (σ) of the graphite particle size distribution was 0.24.

[0292] [Example 10]

[0293] The coke particles with a D50 of 9 μm and starch (fixed carbon 10% by mass) used in Example 1 were stirred and mixed using a mixer to obtain a mixture.

[0294] Next, the obtained mixture was pressed at room temperature using a uniaxial press to a density less than or equal to 1.3 g / cm³. 3 A molded article was obtained. Next, the molded article was heat-treated at 850°C for 8 hours in a nitrogen atmosphere, followed by graphitization at 3000°C for 30 hours. The obtained graphitized article was pulverized to obtain particles. Then, the obtained particles were sieved through a 280-mesh screen to obtain graphite particles for use as the negative electrode material. The volumetric particle size distribution of the graphite particles was determined using a laser diffraction particle size distribution measuring device (SALD3100, Shimadzu Corporation). The results were: D10 = 6.8 μm, D50 = 11.5 μm, D90 = 20.3 μm, and D99.9 = 47.7 μm. The standard deviation (σ) of the graphite particle size distribution was 0.19.

[0295] [Comparative Example 1]

[0296] As the raw material for graphite particles, flat coke particles with a D50 of 16 μm are used, which are derived from petroleum-derived roasted coke (semi-needle coke).

[0297] The obtained coke particles (85 parts by mass), coal tar pitch (15 parts by mass), and graphitization catalyst SiC (15 parts by mass relative to the total of 100 parts by mass of the coke particles and coal tar pitch) were kneaded together using a kneader. Otherwise, the same procedure as in Example 1 was followed to produce graphite particles.

[0298] The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite particles. The results are shown in Table 1.

[0299] [Comparative Example 2]

[0300] The raw coke used in Example 1 was pulverized and classified using a roller mill to obtain flat coke particles with a D50 of 14 μm. These coke particles were packed into a graphitization container without being mixed with coal tar pitch and calcined at 850°C to evaporate impurities in the mixture. Then, graphitization was carried out at 3000°C. The obtained particles were then sieved through a 280-mesh screen to obtain graphite particles for use as a negative electrode material. 50% by mass of these graphite particles and 50% by mass of flake-like natural graphite with a D50 of 3 μm were composited using a spheroidizing process to obtain graphite composite particles. The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite composite particles. The results are shown in Table 1.

[0301] [Comparative Example 3]

[0302] As a raw material for graphite particles, raw coke (needle coke) derived from petroleum is used.

[0303] The coke was coarsely pulverized using a hammer mill. The coarsely pulverized material was sieved using a 3mm sieve, and the sieved material was sieved using a 1mm sieve to recover particles with a diameter of 1mm to 3mm. The obtained particles were then ground using a roller mill to obtain particles with an average diameter of 200μm. These particles were then further pulverized and classified using a roller mill to obtain flat coke particles with a D50 of 16μm. These coke particles were packed into a graphitization container without mixing with coal tar pitch and calcined at 850°C to evaporate impurities in the mixture, followed by graphitization at 3000°C. The obtained particles were then sieved through a 280-mesh screen to obtain graphite particles, which were used as the negative electrode material. The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite particles. The results are shown in Table 1.

[0304] [Compare Examples 4 and 5]

[0305] Petroleum-derived roasted coke (needle coke) was pulverized and classified using a roller mill to obtain flat coke particles with a D50 of 12 μm. These coke particles were then packed into a graphitization container without mixing with coal tar pitch and calcined at 850°C to evaporate impurities in the mixture. Graphitization was then performed at 3000°C or 2800°C. The resulting particles were then sieved through a 280-mesh screen to obtain graphite particles, which were used as the negative electrode material. The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite particles. The results are shown in Table 1.

[0306] [Comparative Example 6]

[0307] Using coke particles with a D50 of 12 μm, which were used in Comparative Examples 4 and 5 to produce graphite particles, the graphitization temperature was changed to 2600 °C. Otherwise, the operation was the same as in Comparative Examples 4 and 5 to obtain graphite particles as a negative electrode material.

[0308] The same procedure as in Example 1 was followed to determine the volumetric particle size distribution of the graphite particles. The results are shown in Table 1.

[0309] Table 1 below shows the manufacturing conditions of the graphite particles and coated graphite particles used as negative electrode materials, as well as the results of the particle size distribution of the graphite particles and coated graphite particles. It should be noted that the units for coke content and binder content in Table 1 refer to "parts by mass". The fixed carbon content (mass%) of the binder in Table 1 refers to the ratio relative to 100% by mass of the total coke and binder (before graphitization).

[0310] [Table 1]

[0311]

[0312] The negative electrode materials obtained in each embodiment and comparative example were subjected to the following physical property measurements and evaluations. The results are shown in Tables 2 and 3.

[0313] (Specific surface area)

[0314] The negative electrode material was filled into the sample cell, and a sample was obtained by pretreatment at 200°C while degassing under vacuum. Nitrogen gas was adsorbed onto the obtained sample using a gas adsorption device (ASAP2010, manufactured by Shimadzu Corporation). The specific surface area of ​​the obtained sample was determined by BET analysis using the 5-point method.

[0315] (Tap density)

[0316] 150cm 3 100 cm³ of graphite particle sample powder was added to a graduated flat-bottomed test tube (manufactured by Kurumichi Scientific Instruments Co., Ltd., KRS-406). 3 The graduated flat-bottomed test tube is then stoppered. Before dropping the test tube, the 0-times tapped density is determined from the mass and volume of the sample powder. Next, the 30-times tapped density and the 250-times tapped density are determined from the mass and volume of the sample powder after dropping the test tube from a height of 5 cm 30 times and 250 times, respectively.

[0317] (degree of graphitization)

[0318] Ten or 20 parts by weight of silicon powder (e.g., NIST SRM640f) were mixed with a graphite sample in an agate mortar for 5 minutes. The resulting mixture was then placed in an X-ray diffraction specimen holder. Using an X-ray diffraction apparatus (e.g., Rigaku X-ray diffraction Analyzer MultiFlex), the diffraction angles corresponding to the (002) plane of graphite and the (111) plane of silicon were measured using CuKα rays (2θ = 25°–29°).

[0319] The observed diffraction angles of silicon and graphite are corrected using the theoretical diffraction angle of Si (2θ = 28.441°), thus determining the correct diffraction angle of graphite.

[0320] The interplanar spacing of the d(002) plane of the negative electrode material was calculated using Bragg's formula (2dsinθ=nλ). The degree of graphitization is calculated using the following formula.

[0321] Degree of graphitization = [(3.44 - interplanar spacing) / (0.086)] × 100

[0322] (R value)

[0323] The R value of the negative electrode material was determined by measuring the Raman spectrum obtained using a Raman spectroscopy measuring device (Horiba Manufacturing Co., Ltd., XploRAPLUS) with the following range as the baseline and under the following conditions.

[0324] -Determination conditions for Raman spectroscopy-

[0325] Laser wavelength: 532nm

[0326] Laser intensity: greater than or equal to 100mW

[0327] • Attenuation filter: 1%

[0328] • Irradiation intensity: 1mW

[0329] • Measurement range: 1000cm -1 ~1800cm -1

[0330] • Irradiation time: 30 seconds

[0331] • Irradiation area: 1μm 2

[0332] • Baseline (D-band): 1100cm -1 ~1470cm -1

[0333] • Baseline (G band): 1450cm -1 ~1710cm -1

[0334] • Cumulative count for 1 particle: 2 times

[0335] • Number of particles measured: 30 particles

[0336] (Compression load)

[0337] 3.0g of negative electrode material was filled into a 15mm diameter mold and compressed at a constant speed of 10mm / min using an Autograph (manufactured by Shimadzu Corporation). During compression, the distance from the bottom surface of the negative electrode material to the pressing surface was measured, and multiplied by the bottom area of ​​the mold to obtain the volume of the negative electrode material. The density under pressure was calculated from the obtained volume of the negative electrode material. A load sensor was installed on the Autograph's pressure hammer to achieve a predetermined density of 1.7g / cm³. 3 The applied pressure (kN / cm) 2 Set as compression load.

[0338] (Rebound rate)

[0339] 3.0 g of negative electrode material was filled into a 15 mm diameter mold and compressed at a constant speed of 10 mm / min using an Autograph (manufactured by Shimadzu Corporation). Then, the pressure was released, and the density after pressure release was measured when the compression surface stopped moving due to elasticity. The baseline density was 1.7 g / cm³. 3 The absolute value of the density difference between the rebound negative electrode material and the density of the rebound negative electrode material divided by the density 1.7 g / cm³ 3 Multiply the obtained value by 100 to calculate the rebound rate (%).

[0340] (Electrode orientation)

[0341] The negative electrode for lithium-ion secondary batteries is fabricated as follows, and the electrode orientation is evaluated under the conditions shown below.

[0342] - Fabrication of the negative electrode for lithium-ion secondary batteries-

[0343] Graphite particles (97.6 parts by weight), carboxymethyl cellulose (CMC) (1.2 parts by weight), and styrene-butadiene rubber (SBR) (1.2 parts by weight) were mixed to prepare a slurry. This slurry was then applied to the glossy surface of electrolytic copper foil at a coating weight of 10 g / cm². 2 The slurry was coated using a specific method, pre-dried at 90°C for 2 hours, and then adjusted to an electrode density of 1.65 g / cm³ using a roller press. 3Then, it is dried at 120°C for 4 hours under a vacuum atmosphere to perform a curing process, thereby forming a negative electrode material layer on the electrolytic copper foil to obtain a negative electrode for lithium-ion secondary batteries.

[0344] -Evaluation of Electrode Orientation-

[0345] The obtained lithium-ion secondary battery was shaped into a negative electrode with a width of 5 cm and an area of ​​600 cm². 2 The long strip-shaped sheet was pressed using a roller press with a hydraulic pressure of 4t. The linear pressure at this point was 4t / 5cm = 0.8t / cm. The pressed negative electrode was placed in the sample cell for X-ray diffraction. Using an X-ray diffraction apparatus (Rigaku X-ray Diffractometer MultiFlex), the X-ray diffraction pattern (2θ = 25.5°–27.5°, 76.5°–78.5°) using CuKα rays was measured under the following conditions: scanning speed 0.25° / min, tube voltage 40kV, tube current 30mA, divergence slit 1°, scattering slit 1°, and receiving slit 0.3mm. The peak intensity (I002) of the obtained 002 diffraction line was calculated. 002 The peak intensity of the 110 diffraction line (I) 110 The ratio of I to ) 002 / I 110 Set this value as the electrode orientation.

[0346] (Discharge capacity)

[0347] The lithium-ion secondary battery prepared as described above was placed in a thermostatic bath set to 25°C and charged at a constant current of 0.2C until the voltage reached 0V (V vs. Li / Li). + Then, it is charged at a constant voltage of 0V until the current reaches 0.02C. Next, after a 30-minute rest, it is discharged at a constant current of 0.2C until the voltage reaches 1.5V (V vs. Li / Li). + ). Calculate the discharge capacity at this time.

[0348] (SOC-Li (Li precipitation resistance))

[0349] The negative electrode obtained above was used to fabricate a lithium-ion secondary battery, and the resistance to Li precipitation was evaluated as follows.

[0350] -Making of Lithium-ion Secondary Batteries-

[0351] Using the above-obtained negative electrode, metallic lithium as the counter electrode, a mixture of ethylene carbonate / ethyl methyl carbonate (3:7 volume ratio) and vinylene carbonate (VC) (1.0 wt%) containing 1 M LiPF6 as the electrolyte, a polyethylene microporous membrane with a thickness of 25 μm as the separator, and a copper plate with a thickness of 250 μm as the spacer, a coin battery as a lithium-ion secondary battery is manufactured.

[0352] -Evaluation of Li precipitation resistance-

[0353] The fabricated lithium-ion secondary battery was placed in a thermostatic bath set to 25°C and charged at a constant current of 0.1C until the voltage reached 0.005V (V vs. Li / Li). + Then, it is charged at a constant voltage of 0.005V until the current reaches 0.05C. Next, after a 30-minute rest, it is discharged at a constant current of 0.2C until the voltage reaches 1.5V (Vvs.Li / Li). + The discharge capacity of the third cycle was set to 1C in the Li deposition experiment. The fourth cycle was charged at a current density of 3C, the discharge capacity of the third cycle, for 20 minutes, with a control voltage of 1.5V. The differential distribution plot (dV / dQ, where V is voltage and Q is capacitance) of the obtained charging curve for the fourth cycle is shown below. Figure 1 The first inflection point in the equation is set as the starting point of Li deposition. The capacity at this point is expressed as a percentage of the discharge capacity of the third cycle (or the charge capacity of the fourth cycle, which is set to the same capacity), and the Li deposition tolerance is evaluated. The results are shown in Table 3.

[0354] (Input characteristics)

[0355] For various graphite particles other than those in the embodiments and comparative examples, the physical property values ​​shown in Tables 2 and 3 were investigated. The results show that when the compressive load is high and the D50 is low, there is a tendency for the Li precipitation resistance, which is related to the battery's input characteristics, to improve. Therefore, the compressive load (kN / cm²) is... 2 D50 (μm) and D50 (μm) were set as explanatory variables, and Li precipitation tolerance was set as the target variable for regression analysis. The result was regression equation (2). Coefficient of determination R 2 It is 0.84.

[0356] Li precipitation tolerance = 11.3x - 0.66y + 1.4…(2)

[0357] The compressive load (kN / cm) measured in each embodiment and comparative example 2Substituting D50 (μm) and D50 (μm) into equation (2) above, this value is used as the evaluation value of the input characteristic. It is believed that there is a tendency that the higher the evaluation value of this input characteristic, the higher the measured value of Li precipitation resistance.

[0358] (curvature)

[0359] In Example 6 and Comparative Example 1, a negative electrode for lithium-ion secondary batteries was obtained by forming a negative electrode material layer on an electrolytic copper foil according to the same steps as the evaluation of electrode orientation.

[0360] Using the obtained negative electrode for lithium-ion secondary batteries, the tortuosity is determined. The tortuosity is the ratio of the tortuosity L (μm), which is the distance L (μm) that travels through the voids inside the negative electrode material layer from one surface to another in the thickness direction, to the thickness T (μm) of the negative electrode material layer, i.e., L / T.

[0361] Specifically, X-ray CT measurements were performed using a microfocus X-ray CT system SMX-160CTS (manufactured by Shimadzu Corporation) under the following conditions: tube voltage 48kV, SID axis 350mm, SOD axis 3mm, multiple cumulative scans 2, and slice spacing 0.001065mm. It should be noted that the electrodes were cut into 2mm × 15mm strips for measurement. Using the obtained CT images, 3D analysis was performed using EXFactVR and ExFact Analysis for Porous Particles (both manufactured by Visual Science Corporation, Japan). The minimum value of the tortuous path through all voids inside the negative electrode material layer from the voids on the surface of the negative electrode material layer in the thickness direction to the voids on the surface of the electrolytic copper foil was determined, and its arithmetic mean was set as the tortuous path length L (μm). Then, the tortuous path length L was divided by the thickness T (μm) of the negative electrode material layer to obtain the tortuosity. It should be noted that if there are multiple tortuous paths from a gap on the surface of the electrolytic copper foil to the surface of the negative electrode material layer in the thickness direction, the value of the smallest tortuous path should be selected.

[0362] The tortuosity of Example 6 was 1.585, while that of Comparative Example 1 was 1.712. The tortuosity of Example 6 was smaller than that of Comparative Example 1, therefore, based on the results shown in Table 3, it is inferred that the Li precipitation resistance was excellent.

[0363] [Table 2]

[0364]

[0365] [Table 3]

[0366]

[0367] The evaluation criteria for each physical property in Table 3 are as follows.

[0368] (D50)

[0369] A: The D50 of the negative electrode material is less than or equal to 11.0 μm.

[0370] B: The D50 of the negative electrode material is greater than 11.0 μm and less than or equal to 14.5 μm.

[0371] C: The D50 of the negative electrode material is greater than 14.5 μm and less than or equal to 17.0 μm.

[0372] D: The D50 of the negative electrode material exceeds 17.0 μm.

[0373] (Specific surface area)

[0374] A: The specific surface area of ​​the negative electrode material is 2.0 m². 2 / g~6.0m 2 / g.

[0375] B: The specific surface area of ​​the negative electrode material is less than 2.0 m². 2 / g.

[0376] C: The specific surface area of ​​the negative electrode material exceeds 6.0 m². 2 / g.

[0377] (degree of graphitization)

[0378] A: The graphitization degree of the negative electrode material is greater than or equal to 92.0%.

[0379] B: The graphitization degree of the negative electrode material is greater than or equal to 90.0% and less than 92.0%.

[0380] C: The graphitization degree of the negative electrode material is less than 90.0%.

[0381] (Compression load)

[0382] A: The compressive load of the negative electrode material is greater than or equal to 2.80 kN / cm. 2 .

[0383] B: The compressive load of the negative electrode material is greater than or equal to 2.30 kN / cm. 2 And less than 2.80 kN / cm 2 .

[0384] C: The compressive load of the negative electrode material is greater than or equal to 1.90 kN / cm. 2 And less than 2.30 kN / cm 2 .

[0385] D: The compressive load of the negative electrode material is less than 1.90 kN / cm. 2 .

[0386] (Electrode orientation)

[0387] A: The value of electrode orientation is less than or equal to 300.

[0388] B: The value of electrode orientation is greater than 300 and less than or equal to 400.

[0389] C: The value of electrode orientation is greater than 400 and less than or equal to 999.

[0390] D: The value of electrode orientation exceeds 999.

[0391] The evaluation criteria for each value representing the performance of lithium-ion secondary batteries in Table 3 are as follows.

[0392] (Discharge capacity)

[0393] A: The discharge capacity of a lithium-ion secondary battery is greater than or equal to 350 Ah / kg.

[0394] B: The discharge capacity of lithium-ion secondary batteries exceeds 340Ah / kg and is less than 350Ah / kg.

[0395] C: The discharge capacity of lithium-ion secondary batteries exceeds 330Ah / kg and is less than or equal to 340Ah / kg.

[0396] D: The discharge capacity of a lithium-ion secondary battery is less than or equal to 330 Ah / kg.

[0397] (Li precipitation resistance)

[0398] A: The Li deposition tolerance of lithium-ion secondary batteries is greater than or equal to 30%.

[0399] B: The Li deposition tolerance of lithium-ion secondary batteries is greater than or equal to 25% and less than 30%.

[0400] C: The Li deposition tolerance of lithium-ion secondary batteries is greater than or equal to 20% and less than 25%.

[0401] D: The Li deposition tolerance of lithium-ion secondary batteries is less than 20%.

[0402] (Evaluation value of input characteristic)

[0403] A: The evaluation value of the input characteristic is greater than or equal to 30.

[0404] B: The evaluation value of the input characteristic is greater than or equal to 25 and less than 30.

[0405] C: The evaluation value of the input characteristic is greater than or equal to 20 and less than 25.

[0406] D: The evaluation value of the input characteristic is less than 20.

[0407] Table 3 shows that the high evaluation values ​​of input characteristics and high degree of graphitization confirm the excellent discharge capacity and Li precipitation resistance of the lithium-ion secondary battery.

[0408] The disclosure of PCT / JP2021 / 003761 filed on February 2, 2021, is incorporated herein by reference in its entirety.

[0409] All documents, patent applications and technical standards described herein are incorporated herein by reference to the same extent as the specific documents, patent applications and technical standards which are incorporated herein by reference.

Claims

1. A negative electrode material for lithium-ion secondary batteries, comprising graphite particles as follows: (The graphite particles will be compacted to 1.7 g / cm³ in Autograph measurements.) 3 Let the required compression load be x, then x ≥ 2.0, and the unit is kN / cm. 2 Let y be the particle size at which the cumulative particle size distribution from the small diameter side reaches 50% in the volume reference particle size distribution determined by laser diffraction. Then 5.0≤y≤20.0, the unit is μm. The x and y satisfy the following equation (1), and the degree of graphitization satisfies greater than or equal to 90.0%. 11.3x-0.66y+1.4≥14.5…(1), The peak intensity I of the 002 diffraction line obtained by X-ray diffraction measurement of the negative electrode formed using a negative electrode material for lithium-ion secondary batteries after being pressed at 0.8 t / cm is... 002 Peak intensity I of 110 diffraction line 110 The ratio is I 002 / I 110 Less than or equal to 350.

2. A negative electrode material for lithium-ion secondary batteries, comprising graphite particles such that, when forming a negative electrode material layer using the negative electrode material for lithium-ion secondary batteries, the ratio of the tortuous path length L (the distance L that passes through the voids inside the negative electrode material layer from one surface to another in the thickness direction) to the thickness T of the negative electrode material layer, i.e., L / T, satisfies less than or equal to 1.7, wherein the units of the tortuous path length L and the thickness T are μm. The peak intensity I of the 002 diffraction line obtained by X-ray diffraction measurement of the negative electrode formed using a negative electrode material for lithium-ion secondary batteries after being pressed at 0.8 t / cm is... 002 Peak intensity I of 110 diffraction line 110 The ratio is I 002 / I 110 Less than or equal to 350.

3. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the surface of the graphite particles is not coated with low-crystallinity carbon.

4. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the content at 1300 cm⁻¹ is determined by Raman spectroscopy. -1 ~1400cm -1 Peak intensity I within the range D With 1580cm -1 ~1620cm -1 Peak intensity I within the range G The ratio is I D / I G If we define it as the R value, then the R value of the graphite particles is 0.10~0.

40.

5. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the surface of the graphite particles is coated with low-crystallinity carbon. The value at 1300 cm⁻¹ was determined by Raman spectroscopy. -1 ~1400cm -1 Peak intensity I within the range D With 1580cm -1 ~1620cm -1 Peak intensity I within the range G The ratio is I D / I G If we define it as the R value, then the R value of the graphite particles is 0.20~0.

60.

6. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the particle size of the graphite particles is 0.1 μm to 7.0 μm when the cumulative particle size distribution on a volume basis determined by laser diffraction reaches 10% from the small diameter side.

7. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the zero-tap density of the graphite particles is 0.3 g / cm³. 3 ~0.6g / cm 3 .

8. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the 30-beat tap density of the graphite particles is 0.4 g / cm³. 3 ~0.7g / cm 3 .

9. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the tap density of the graphite particles after 250 vibrations is 0.7 g / cm³. 3 ~1.1g / cm 3 .

10. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the specific surface area of ​​the graphite particles, determined by nitrogen adsorption at 77 K, is 0.2 m². 2 / g~6.0m 2 / g.

11. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the particle size distribution D90 / D10 of the graphite particles is 3.0~7.

0.

12. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the graphite particles comprise composite particles formed by the aggregation or combination of multiple graphite particles.

13. A negative electrode material composition for lithium-ion secondary batteries, comprising the negative electrode material for lithium-ion secondary batteries, a binder, and a solvent as described in any one of claims 1 to 12.

14. A negative electrode for a lithium-ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for a lithium-ion secondary battery as described in any one of claims 1 to 12.

15. A lithium-ion secondary battery comprising a negative electrode, a positive electrode, and an electrolyte as described in claim 14 for a lithium-ion secondary battery.

Citation Information

Patent Citations

  • Negative electrode active material for lithium secondary battery, negative electrode including the same and lithium secondary battery

    JP2005302725A

  • Negative electrode material for lithium-ion secondary cell, method for manufacturing negative electrode material for lithium-ion secondary cell, negative electrode material slurry for lithium-ion secondary cell, negative electrode for lithium-ion secondary cell, and lithium-ion secondary cell

    WO2015147012A1

  • Nonaqueous battery and method of producing the same

    CN108807844A

  • Evaluation method and manufacturing method for electrode

    JP2015041434A

  • Catalytically active additive for petroleum or coal-derived coke

    JP2019510714A